ANALISIS IMPLEMENTASI NILAI-NILAI KESOPANAN OLEH GURU SOSIOLOGI KELAS XI IPS 3 MAN 1 PONTIANAK - Bastari, Saptia; Sulistyarini, Sulistyarini; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstractThe title of this research was â€œAnalysis of the Implementation of Politeness Values by Sociology Teachers in Class XI IPS 3 MAN 1 Pontianakâ€. The purpose of this study was to determine the process of implementing politeness values implemented by students under the guidance of sociology teachers in class XI IPS 3 MAN 1 Ponianak and the impact of implementing politeness values applied by students under the guidance of sociology teachers in class XI IPS 3 MAN 1 Pontianak. The research method used was descriptive method with qualitative research forms. The data source of his research was the sociology Teacher and Students of XI IPS 3 MAN 1 Pontianak class. Data collection techniques in this study were through observation, interviews and documentation, while the data collection tools used were observation guides, interviews guides and documentation, while the data collection tools used were observation guides, interview guides and documentation tools. The analysis in this study was presented in a descriptive qualitative manner using 4 informants. The result showed that 1. In its application, it was done by always giving advice and reprimands to student directly both in the classroom and outside the classroom. 2. The impact of the implementation of politeness values had a lot of positive impacts on students, as a whole in the classroom attributes, speak and be polite to teachers and peers, and greet each other in the scope of the school. Â Keywords: Implementation, Politeness, Teacher.